2021
DOI: 10.3390/ijms23010172
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Analogs Regulate the Vitamin D System and Cell Viability in Ovarian Cancer Cells

Abstract: Background: Ovarian cancer (OC) is one of the most lethal cancers in women. The active form of vitamin D3, 1,25-dihydroxyvitamin D3 (1,25D3, calcitriol) has anticancer activity in several cancers, including ovarian cancer, but the required pharmacological doses may cause hypercalcemia. We hypothesized that newly developed, low calcemic, vitamin D analogs (an1,25Ds) may be used as anticancer agents instead of calcitriol in ovarian cancer cells. Methods: We used two patient-derived high-grade serous ovarian canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…One study reported higher levels in ovarian tumors compared with healthy tissue [31], while others found that the VDR level was lower in tumors than in normal ovaries [32]. Treatment of OC cell lines with 1,25D3 or its analogs has no effect on VDR mRNA levels, while it might increase protein levels in a cell line-dependent manner [30,33]. Interestingly, the effect of 1,25D3 or its analogs on the expression of CYP24A1 in different OC cell lines does not predict their anticancer effect [30].…”
Section: Mechanism Of Anticancer Activity In Ovarian Cancer Models In...mentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported higher levels in ovarian tumors compared with healthy tissue [31], while others found that the VDR level was lower in tumors than in normal ovaries [32]. Treatment of OC cell lines with 1,25D3 or its analogs has no effect on VDR mRNA levels, while it might increase protein levels in a cell line-dependent manner [30,33]. Interestingly, the effect of 1,25D3 or its analogs on the expression of CYP24A1 in different OC cell lines does not predict their anticancer effect [30].…”
Section: Mechanism Of Anticancer Activity In Ovarian Cancer Models In...mentioning
confidence: 99%
“…The heterogeneity of OC is mirrored by the diversity of the existing cell lines. Even those cell lines that were obtained from the same type of tumors show high diversity in their sensitivity to vitamin D and its analogs [30]. This might be due to differences in their mutational landscape, but also in the expression of the components of the vitamin D system.…”
Section: Mechanism Of Anticancer Activity In Ovarian Cancer Models In...mentioning
confidence: 99%
“…They also have a low resistance to vitamin D metabolizing enzymes [ 10 ]. The current search is for vitamin D analogs of therapeutic potential against leukemia [ 7 , 11 , 12 ] and solid tumors, including breast [ 13 ], lung [ 14 ], prostate [ 15 ], colorectal [ 16 , 17 ], skin [ 18 ], and ovarian cancer [ 19 ]. We have developed analogs of 1,25D that exceed the potency of the parent 1,25D against cancer cells in vitro and in vivo, and that are less calcaemic and more enzymatically stable [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This shows the influence of the exocyclic methylene on the biological activity of vitamin D analogues and its importance in vitamin-D based drug design. Very recently, we first demonstrated that vitamin D analogues might be a new treatment for ovarian cancer [ 9 ].…”
Section: Introductionmentioning
confidence: 99%